Effects of Supplementing Corn Silage to Fall-Calving Heifers and Cows Grazing Tall Fescue on Cow Performance - Jaymelynn K. Farney; Tatiana M. Jones (Kansas Agricultural Experiment Station Research Reports, 2025)
The objective was to test the effect of fescue cultivars and supplemental feeding of cows grazing fescue pastures on cow performance and pasture management. Primiparous and multiparous Angus-based crossed cows (n = 48) averaging 140 ± 0.5 days of gestation at turnout, were randomly allocated and stratified to pasture treatment by parity. Each pasture contained three cows of different ages, consisting of a young (first-calf heifer), middle-aged (3-5 yrs.), and old (≥ 6 yrs.) cow. Treatment was a 2 by 2 factorial design with two types of pasture (toxin producing: TOXIC or non-toxin producing fescue: NONTOXIC) and two levels of supplemental feeding (non-supplemented: NON or supplemented at 1% of body weight on a dry matter basis of corn silage: SUPP). Toxic fescue pastures consisted of K-31 endophyte infected tall fescue (n = 8) tested at 1709 ppm ± 0.36 for ergot alkaloids with an 89.1% infection rate. Non-toxic pastures consisted of novel (MaxQ) and endophyte free varieties (n = 8). Cows were fed silage (32-42% dry matter and 7.83% crude protein) daily in fence-line bunks, with feeding amount being adjusted at each weigh date. Cows were weighed on 2 consecutive days prior to turnout ( middle of the second trimester), beginning of the third trimester, 2 weeks prior to the estimated calving date for herd, and at peak lactation ( 60 days after calving). Body weight (BW), body condition score (BCS), hair score (based on a 1-5 scale; HS), hair length measured over the 3rd rib (HL), and rump fat (RF) measurements were taken at each weigh date during gestation. Calves were weighed at birth and used in weigh-suckle-weigh to estimate milk output. Forage accumulation (FA) and forage mass (FM) were estimated every 28 days using the paired-cage method. There were no grass type x supplementation interactions (P > 0.19) for any measurement, other than HS and HL. Prior to calving, there was a tendency for cows grazing NONTOXIC to have heavier weights (P = 0.10); this continued through peak lactation (P = 0.10). Supplementation did not affect BW (P > 0.32), BCS (P > 0.22), or RF (P > 0.21) during gestation; but during lactation SUPP increased BCS (P = 0.007) over NON. Hair length and HS were greater for cows grazing TOXIC pastures at the beginning of third trimester (P = 0.06) and immediately prior to calving (P = 0.04). NONTOXIC-NON cows had a greater reduction in HL than those grazing TOXIC-NON with supplementation on both grass types being intermediate (P = 0.05). Calf birth weight and estimates of milk output were not different for grass type or supplementation (P > 0.23). Forage mass tended to be 11% greater in TOXIC pastures than NONTOXIC (P = 0.06) and SUPP pastures tended to have 6% greater FM than NON (P = 0.09). Non-toxic pastures, overall, result in greater cattle performance. Supplementation did not offset toxicity but did result in greater available forage.
Keywords: Fescue toxicosis; endophyte; cow-calf; gestation